Systematic literature review on green IT practice and organizational sustainability - Abdul Kader Jailani, Sri Fatiany; Abdullah, Lili Marziana (2017)
– The current research environment is witnessing the emergence of a prevalent method in the analysis of secondary data. The Systematic Literature Review (SLR) is becoming one of the most valued methods of generating reliable information. The implementation of SLR requires the formulation of research questions (RQs) for the review purposes, which will be used to guide the search and extraction process. In this study, SLR has been utilised to extend the studies regarding Green ICT practice and organisational sustainability. Sustainability is not a new word, and the same goes with Green IT practice. Many areas of study are now focused on the matter of sustainability in an attempt to minimise compromising the well-being of future generations. Furthermore, organisational sustainability allows the organisations to reach their goal. Nevertheless, this effort requires a good care of the economic, societal and environmental welfare. From the SLR, 57 out of 150 studies have been identified to discuss the issues of Green IT and the organisation. From 57 studies, only 18 studies focused on Green IT practice. 12 out of the 18 studies, discussed the types of Green IT practice. The studies concentrated on factors that influence the implementation of Green IT. A total of 17 factors were identified from five different sources. This study also looked at the measurement used to assess organisational sustainability that includes Green IT practice. This paper will be useful for the organisation as a guide to bring greener technologies and more environmentally responsible practices and strategies in organising.